B Cell Receptor Signaling and Protein Kinase D2 Support Regulatory B Cell Function in Pancreatic Cancer - Michaud, Daniel; Mirlekar, Bhalchandra; Steward, Colleen; Bishop, Gail; Pylayeva-Gupta, Yuliya (Frontiers in Immunology, 2022)
B cells can act as potent suppressors of anti-tumor T cell immunity, presenting a mechanism of resistance to immunotherapy. In pancreatic ductal adenocarcinoma, B cells can display a T cell-suppressive or regulatory phenotype centered on the expression of the cytokine Interleukin 35 (IL-35). While B cell-mediated immunosuppression presents a barrier to anti-tumorigenic T cell function, it is not clear how regulatory B cell function could be targeted, and the signals that promote this suppressive phenotype in B cells are not well understood. Here we use a novel IL-35 reporter model to understand which signaling pathways are important for immunosuppressive properties in B cells. In vitro analysis of IL-35 reporter B cells revealed a synergy between the BCR and TLR4 signaling pathways is sufficient to induce IL-35 expression. However, in vivo, B cell receptor activation, as opposed to MyD88 signaling in B cells, is central to B cell-mediated suppression and promotion of pancreatic cancer growth. Further analysis identified protein kinase D2 (PKD2) as being a key downstream regulator of IL-35 expression in B cells. Regulatory B cells with an inactivating mutation in PKD2 failed to produce IL-35 or fully suppress effector T cell function in vitro. Furthermore, inhibition of PKD in B cells decreased tumor growth and promoted effector T cell function upon adoptive transfer into B cell-deficient mice. Collectively, these data provide insight into how regulatory B cell function is promoted in pancreatic cancer and identify potential therapeutic targets to restrain this function.